Margot [videorecording (DVD)] - Palmer, Tony, 1941- (Digital Classics DVD, 2005)
Film about the life of dancer Margot Fonteyn. Contains archival footage including performances with Rudolf Nureyev and others. Meets with those who danced with her and knew her. Ballets featured include: Romeo and Juliet, Swan Lake, Giselle, The sleeping beauty, Marguerite and Armand, and the Nutcracker.